Studies on Tissue Thromboplastin - Its Splitting into Two Separable Parts - Hvatum, M; Prydz, H (Thrombosis and Haemostasis, 1969)
1. Sodium deoxycholate (DOC) splits tissue thromboplastin into two inactive parts, fraction A and fraction B, separable by gel filtration in the presence of DOC.2. By recombination and subsequent removal of the DOC, the fractions reaggregate and regain full thromboplastic activity.3. Fraction A consists mainly of protein, while phospholipid is the main constituent of fraction B.